Electrolyte additives for high performance iodine-based or bromine-based electrochemical devices
Patent Information
- Application Number
- CN202580020332.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-30
- Filing Date
- 2025-01-30
- Publication Date
- 2026-10-20
AI Technical Summary
[0030]第一、第二、第三、第四或第五方面的一些实施方案中,所述电化学装置,在44.0%的放电深度以及室温下具有约每月11.7%容量损失率的低自放电率。在一些实施方案中,所述电化学装置在750次循环后表现出约94.0%容量保持率的长寿命。在一些实施方案中,所述电化学装置在大于15 mg·cm–2的面负载量下以20 mA·cm–2(~6.7 C)的高倍率下保持其容量的约83.5%。在一些实施方案中,所述电化学装置在2500次循环后表现出约68.2%的放电深度(DOD)和约90.0%的容量保持率。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] Priority information This application claims priority to Australian Provisional Patent Application No. 2024900214, filed on January 30, 2024, entitled “Electrolyte Additive for High-Performance Iodine-Based or Bromine-Based Electrochemical Devices,” the contents of which are incorporated herein by reference in their entirety. Technical Field
[0002] This disclosure generally relates to aqueous electrochemical devices, such as iodine-based or bromine-based batteries. In particular, this disclosure relates to electrolyte additives for aqueous electrochemical devices, and to electrochemical devices comprising such additives. Background Technology
[0003] The energy crisis and increasingly severe environmental problems have driven the rapid development of reliable, low-cost, and environmentally friendly electrochemical energy storage devices. Among these, organic electrolyte-based batteries exhibit high energy density and are theoretically suitable for large-scale energy storage. However, these batteries face inherent instability and safety issues due to their use of expensive but volatile and flammable organic solvents (such as dimethyl carbonate and diethyl carbonate) and chemically unstable and toxic salts (such as lithium hexafluorophosphate (LiPF6)). The risk of organic solvent leakage is also a concern for large-scale energy storage. Aqueous batteries show promise in addressing these issues and, due to their cost-effectiveness, high ionic conductivity, and significantly improved safety, demonstrate great potential for large-scale energy storage.
[0004] Iodine in seawater (approximately 50 µg·L) - ¹) and bromine (approximately 65 mg·L⁻¹) - ¹) The abundant reserves of iodine and bromine, along with the highly reversible redox chemistry of iodine or bromine, make iodine-based or bromine-based batteries promising and inexpensive energy storage systems. Therefore, iodine-based and bromine-based batteries have received increasing attention, such as metal-iodine or metal-bromine batteries, including aqueous zinc-iodine (Zn-I2) batteries, aqueous zinc-bromine (Zn-Br2) batteries, aqueous lithium-iodine (Li-I2) batteries, non-aqueous lithium-iodine (Li-I2) batteries, aqueous sodium-iodine (Na-I2) batteries, non-aqueous magnesium-bromine (Mg-Br2) batteries, aqueous aluminum-iodine (Al-I2) batteries, and non-aqueous aluminum-iodine (Al-I2) batteries.
[0005] Aqueous zinc-based batteries with high safety and low cost provide a candidate for large-scale energy storage. [1] Among zinc-based batteries, rechargeable Zn-I2 batteries are particularly attractive due to the abundance of iodine in seawater [2], the stability of metallic zinc in water, and high specific capacity (211 mAh·g). 碘 -1 [3] and high discharge potential plateau (relative to Zn / Zn) 2+(1.38 V) [4]. Furthermore, I at the positive electrode - The liquid phase conversion mechanism of / I2 endows the Zn-I2 system with excellent rate performance. [5] In addition, compared with rechargeable aqueous Zn-I2 batteries, rechargeable aqueous Zn-Br2 batteries can exhibit a higher theoretical specific capacity (355 mAh·g). -1 ) and a higher theoretical voltage plateau (relative to Zn / Zn 2+ (1.85 V).
[0006] However, existing rechargeable aqueous and non-aqueous metal-iodine or metal-bromine batteries are still far from satisfactory, due to challenges such as intermediate dissolution, severe self-discharge, and metal anode corrosion. [2] In particular, the weak interaction between the positive electrode conductive carrier and iodine / bromine species leads to the dissolution of intermediate polyiodide or polybrominate anions or molecules in aqueous or non-aqueous electrolytes, followed by the migration of polyiodide or polybrominate across the membrane to the metal anode, i.e., the shuttle effect. The shuttle effect caused by polyiodide or polybrominate usually occurs in five steps: (i) formation of long-chain polyhalide anions, (ii) removal of polyhalide anions from the halogen source, (iii) dissolution of polyhalide anions into the electrolyte solution, (iv) migration of polyhalide anions to the anode, and (v) reaction of polyhalide anions with the anode metal. The shuttle effect can lead to irreversible loss of iodine or bromine, anode metal corrosion, rapid capacity decay and low coulombic efficiency, severe self-discharge, and poor cycle stability. [6-8] In aqueous electrolytes, Zn-I2 batteries exhibit reversible Ig... - / I2 redox reaction, in which polyiodide species (e.g., I5) - and I3 - As a highly soluble intermediate, it forms a shuttle effect, leading to irreversible loss of active materials (e.g., Zn) and hindering the improvement of the depth of discharge. [5,11,16] Therefore, it is of great significance to develop an economical electrolyte that can simultaneously stabilize the positive and negative electrodes, thereby improving the utilization rate of iodine-based or bromine-based batteries.
[0007] To address these challenges, several approaches have been proposed, including: designing porous carbon substrates [9-12] to confine polyiodides or polybrominates and suppress shuttle effects; altering the iodine reaction pathway through confinement effects in the pores
[13] ; or implementing protective measures for the Zn anode [8,14,15] to prevent its reaction with I3. - A reaction occurs. Although some good results have been reported, these results are mainly at low electrode loadings (<2 mg·cm⁻¹). -This was achieved in coin cells at high test rates (>5 C). However, the low mass loading and high test current may mask the shuttle effect of the iodine cathode and the side reactions of the Zn anode, making it difficult to effectively apply small-size battery configurations to large-scale energy storage.
[0008] Therefore, there is still a need for a cost-effective electrolyte solution and an electrochemical device containing such electrolyte solution, which can solve or alleviate one or more of the above problems and have practical value in large-scale energy storage. Summary of the Invention
[0009] In a first aspect, this disclosure provides an ionic liquid additive for use in the electrolyte solution of an electrochemical device, and capable of interacting with polyiodide and / or polybrominate species to mitigate the shuttle effect of the electrochemical device.
[0010] In some embodiments of the first aspect, the ionic liquid that can be used as the additive has at least one heteroatom within the conjugated ring. In some embodiments, the heteroatom is selected from nitrogen (N), sulfur (S), and oxygen (O). In some embodiments of these embodiments, the heteroatom is nitrogen (N). In some further embodiments, the ionic liquid that can be used as the additive has two heteroatoms within the conjugated ring. In even further embodiments, the two heteroatoms are nitrogen (N) and sulfur (S), nitrogen (N) and oxygen (O), or both are nitrogen (N).
[0011] In some embodiments of the first aspect, the ionic liquid that can be used as the additive is selected from the group consisting of imidazolium ionic liquids, pyrazolium ionic liquids, oxazolium ionic liquids, thiazolyl ionic liquids, pyridinium ionic liquids, and picolinium ionic liquids. In some embodiments, the ionic liquid additive is a mixture of ionic liquids.
[0012] In some embodiments of the first aspect of this disclosure, the ionic liquid that can be used as the additive includes anions selected from: halide ions, hydroxide ions, carboxylate ions, sulfite ions, sulfate ions (such as hydrogen sulfate and methyl sulfate), sulfonate ions, aminosulfonate ions, carbonate ions, nitrate ions, nitrite ions, perchlorate ions, dicyandiamide ions, thiocyanate ions, sulfonylimide ions, antimony ions, arsenate ions, phosphate ions, phosphonate ions, hypophosphonate ions, phosphite ions, hypophosphonite ions, borate ions, and imide ions. In some embodiments, the ionic liquid that can be used as the additive has anions selected from: Cl... ,Br nitrate (NO3) ), sulfate (SO4 2 ), hydrogen sulfate (HSO4) ), perchlorate (ClO4) Acetate (CH3COO) ), trifluoroacetate (CF3COO) ), trichloroacetic acid (CCl3COO) ), tetrafluoroborate (BF4) ), hexafluorophosphate (PF6) ), hexafluoroantimony (SbF6) ), hexafluoroarsenate (AsF6) ), methyl sulfate (CH3SO4) ), ethyl sulfate (C2H5SO4) ), methanesulfonate (CH3SO3) ), trifluoromethanesulfonate (CF3SO3) ), perfluorobutyrate (C4F9SO3) ), bis(fluorosulfonyl)imide ((FSO2)2N – ), bis(trifluoromethanesulfonyl)imide ((CF3SO2)2N Heptafluorobutyrate (C3F7COO) ) and bis(pentafluoroethanesulfonyl)imide ((C2F5SO2)2N ).
[0013] In some embodiments of the first aspect, the ionic liquid that can be used as the additive has an organic cation, for example, one cation (i.e., a monocationic ionic liquid) and two cations (i.e., a dicationic ionic liquid). In some embodiments, the organic cation is selected from the group consisting of imidazolium cation, pyrazolium cation, oxazolium cation, thiazolium cation, pyridinium cation, and picolinium cation. In some embodiments, the ionic liquid that can be used as the additive has an organic cation selected from the group consisting of imidazolium cation, pyrazolium cation, pyridinium cation, and picolinium cation. In some embodiments of these embodiments, the organic cation is a pyrazolium cation. In other embodiments of these embodiments, the organic cation is a pyridinium cation. In some further embodiments, the organic cation has a substituent selected from the group consisting of alkyl, alkoxy, hydroxyalkyl, cycloalkyl, heterocycloalkyl, alkenyl, alkynyl, aryl, and heteroaryl. In a further embodiment, the organic cation has substituents selected from the group consisting of: C1-C8 alkyl, C1-C8 alkoxy, C1-C8 hydroxyalkyl, C3-C8 cycloalkyl, C3-C8 heterocycloalkyl, C2-C8 alkenyl, C2-C8 alkynyl, C6-C 12 Aryl and C3-C12 Mixed aromatic compounds.
[0014] In some embodiments of the first aspect, the ionic liquid that can be used as the additive has the general formula (I): (I) Among them, R 1 R 2 R 3 R 4 and R 5 Each is independently selected from the group consisting of: H atoms and organic substituents having 1 to 20 carbon atoms, for example 1 to 12 carbon atoms or 1 to 8 carbon atoms, L - It is a compatible anion. In some implementations, R 2 For H, R 1 R 3 R 4 and R 5 Each is independently selected from the group consisting of an H atom and an organic substituent having 1 to 20 carbon atoms. In some further embodiments, the organic substituent having 1 to 20 carbon atoms is selected from the group consisting of alkyl, alkoxy, hydroxyalkyl, cycloalkyl, heterocycloalkyl, alkenyl, ynyl, aryl, and heteroaryl. In even further embodiments, the organic substituent having 1 to 20 carbon atoms is selected from the group consisting of C1-C8 alkyl, C1-C8 alkoxy, C1-C8 hydroxyalkyl, C3-C8 cycloalkyl, C3-C8 heterocycloalkyl, C2-C8 alkenyl, C2-C8 ynyl, C6-C 12 Aryl and C3-C 12 heteroaryl. In some embodiments, L - Selected from those anions described above for ionic liquids in this disclosure.
[0015] In some embodiments of the first aspect, the ionic liquid that can be used as the additive has the general formula (I'): (I') Among them, R 1 and R 3 Each is independently selected from the group consisting of: H atoms and organic groups having 1 to 20 carbon atoms, for example 1 to 12 carbon atoms or 1 to 8 carbon atoms, L - It is a compatible anion. In some implementations, R 1 and R 3 Each is independently selected from the group consisting of: H, C1-C8 alkyl, C1-C8 alkoxy, C1-C8 hydroxyalkyl, C3-C8 cycloalkyl, C3-C8 heterocycloalkyl, C2-C8 alkenyl, C2-C8 alkynyl, C6-C 12Aryl and C3-C 12 heteroaryl. In some further embodiments, R 1 and R 3 Each is independently selected from the group consisting of: C1-C8 alkyl, C1-C8 hydroxyalkyl, and C2-C8 alkenyl. In some embodiments, L - Selected from those anions described above for ionic liquids in this disclosure.
[0016] In some embodiments of the first aspect, the ionic liquid that can be used as the additive has an organic cation selected from the group consisting of: 1-ethyl-3-methylimidazolium ion, 1-propyl-3-methylimidazolium ion, 1-butyl-3-methylimidazolium ion, 1-pentyl-3-methylimidazolium ion, 1-hexyl-3-methylimidazolium ion, 1-ethyl-3-vinylimidazolium ion, 1-octyl-3-methylimidazolium ion, 1-allyl-3-methylimidazolium ion, 1-butyl-2-methylpyrazolium ion, 1-butylpyridinium ion, 1-pentylpyridinium ion, 1-hexyl-3-picolinium ion, 1-hexyl-4-picolinium ion, and 1-(3-hydroxypropyl)-3-methylimidazolium ion.
[0017] In some embodiments, the ionic liquid that can be used as the additive is selected from the group consisting of: 1-Propyl-3-methylimidazolium methanesulfonate, 1-Propyl-3-methylimidazolium methyl sulfate, 1-Propyl-3-methylimidazolium trifluoromethanesulfonate, 1-Propyl-3-methylimidazolium chloride, or 1-Propyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium methanesulfonate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium methanesulfonate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Hexyl-3-methylimidazolium methanesulfonate, 1-Hexyl-3-methylimidazolium methyl sulfate, 1-Hexyl-3-methylimidazolium trifluoromethanesulfonate, 1-Hexyl-3-methylimidazolium chloride, 1-Hexyl-3-methylimidazolium tetrafluoroborate, 1-Hexyl-3-methylimidazolium acetate, or 1-Hexyl-3-methylimidazolium nitrate; 1-Octyl-3-methylimidazolium methanesulfonate, 1-Octyl-3-methylimidazolium methyl sulfate, 1-Octyl-3-methylimidazolium trifluoromethanesulfonate, 1-Octyl-3-methylimidazolium chloride, 1-Octyl-3-methylimidazolium tetrafluoroborate, 1-Octyl-3-methylimidazolium acetate, or 1-Octyl-3-methylimidazolium nitrate; 1-Ethyl-3-vinylimidazolium methanesulfonate, 1-Ethyl-3-vinylimidazolium methyl sulfate, 1-Ethyl-3-vinylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-vinylimidazolium chloride, 1-Ethyl-3-vinylimidazolium tetrafluoroborate, 1-Ethyl-3-vinylimidazolium acetate, or 1-Ethyl-3-vinylimidazolium nitrate; 1-Ethyl-3-methylimidazolium trifluoroacetate, 1-Ethyl-3-methylimidazolium methyl sulfate, 1-Ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-methylimidazolium chloride, 1-Ethyl-3-methylimidazolium tetrafluoroborate, 1-Ethyl-3-methylimidazolium acetate, or 1-Ethyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium trifluoroacetate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Butyl-2-methylpyrazolium bis(trifluoromethanesulfonyl)imide; 1-Butylpyridinium methanesulfonate, 1-Butylpyridinium methyl sulfate, 1-Butylpyridinium trifluoromethanesulfonate, 1-Butylpyridinium chloride, 1-Butylpyridinium tetrafluoroborate, 1-Butylpyridinium acetate, or 1-Butylpyridinium nitrate; 1-Pentylpyridinium trifluoroacetate; 1-Hexyl-3-picolinonium methanesulfonate, 1-Hexyl-3-picolinonium methyl sulfate, 1-Hexyl-3-picolinonium trifluoromethanesulfonate, 1-Hexyl-3-picolinonium chloride, 1-Hexyl-3-picolinonium tetrafluoroborate, 1-Hexyl-3-picolinonium acetate or 1-Hexyl-3-picolinonium nitrate; and 1-Hexyl-4-picolinon methanesulfonate, 1-Hexyl-4-picolinon methyl sulfate, 1-Hexyl-4-picolinon trifluoromethanesulfonate, 1-Hexyl-4-picolinon chloride, 1-Hexyl-4-picolinon tetrafluoroborate, 1-Hexyl-4-picolinon acetate, or 1-Hexyl-4-picolinon nitrate.
[0018] Secondly, this article provides an electrolyte solution for an electrochemical device, wherein the electrolyte solution comprises the ionic liquid additives described in the first aspect.
[0019] Thirdly, this article provides an electrochemical device comprising an electrolyte solution, wherein the electrolyte solution comprises the ionic liquid additive described in the first aspect.
[0020] Fourthly, this article provides the use of ionic liquids as additives to electrolyte solutions in mitigating the shuttle effect in electrochemical devices, wherein the ionic liquid additive is the ionic liquid additive described in the first aspect.
[0021] Fifthly, this article provides a method for mitigating the shuttle effect caused by polyiodide and / or polybrominate species in an electrochemical device, wherein the method comprises introducing the ionic liquid additive described in the first aspect into the electrolyte solution of the electrochemical device.
[0022] In some embodiments of the first, second, third, fourth, or fifth aspects, the electrolyte solution comprises the ionic liquid additive at a concentration of 0.01 M to 0.5 M, or 0.06 M to 0.15 M, or 0.07 M to 0.12 M, or 0.08 M to 0.10 M. In some embodiments, the molar ratio of the ionic liquid additive to the electrolyte is 0.025:1 to 0.1:1, or 0.03:1 to 0.075:1, or 0.035:1 to 0.06:1, or 0.04:1 to 0.05:1.
[0023] In some embodiments of the first, second, third, fourth, or fifth aspects, the electrolyte solution is water-based. In some embodiments, the electrolyte in the electrolyte solution is selected from the group consisting of: ZnSO4, ZnCl2, ZnNO3, zinc acetate, zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2), zinc trifluoromethanesulfonate (Zn(OTf)2), Zn(ClO4)2, and combinations thereof.
[0024] In some embodiments of the first, second, third, fourth, or fifth aspects, the electrochemical device includes a positive electrode and a negative electrode.
[0025] In some embodiments of the first, second, third, fourth, or fifth aspects, the iodine source and / or bromine source serving as the positive electrode active material are contained within the positive electrode and / or the electrolyte solution. In some embodiments, the iodine source and / or bromine source serving as the positive electrode active material is selected from: elemental iodine (I₂), LiI, NaI, KI, ZnI₂, NH₄I, quaternary ammonium iodides (such as trimethylammonium iodide), quaternary ammonium bromides (such as trimethylammonium bromide), triiodomethane (CH₃I), poly(vinylpyrrolidone)-iodine (PVP-I), elemental bromine (Br₂), LiBr, KBr, ZnBr₂, and combinations thereof.
[0026] In some embodiments of the first, second, third, fourth, or fifth aspects, the negative electrode comprises a zinc source, a lithium source, a sodium source, an aluminum source, or a magnesium source as the negative electrode active material.
[0027] In some embodiments of the first, second, third, fourth, or fifth aspects, the electrochemical device is an aqueous electrochemical device. In some embodiments, the electrochemical device is an iodine-based electrochemical device or a bromine-based electrochemical device. In some further embodiments, the aqueous electrochemical device is selected from aqueous metal-iodine electrochemical devices and aqueous metal-bromine electrochemical devices. In some further embodiments, the aqueous electrochemical device is an aqueous zinc-iodine electrochemical device or an aqueous zinc-bromine electrochemical device. In an even further embodiment, the aqueous electrochemical device is an aqueous zinc-iodine electrochemical device, wherein metallic zinc (Zn) is used as the negative electrode active material and elemental iodine (I₂) is used as the positive electrode active material.
[0028] In some embodiments of the first, second, third, fourth, or fifth aspects, the electrochemical device includes a membrane selected from: glass fiber membranes, ceramic membranes, polyolefin membranes, nonwoven membranes, and porous polymer membranes.
[0029] In some embodiments of the first, second, third, fourth, or fifth aspects, the electrochemical device further comprises a conductive agent in the positive electrode and / or the negative electrode. In some embodiments, the conductive agent is selected from: carbon black, Ketjen black, graphene, activated carbon, conductive carbon nanofibers (VGCF), carbon nanotubes (CNTs), multi-walled carbon nanotubes (MWCNTs), and combinations thereof.
[0030] In some embodiments of the first, second, third, fourth, or fifth aspects, the electrochemical device exhibits a low self-discharge rate of approximately 11.7% capacity loss per month at a depth of discharge of 44.0% and at room temperature. In some embodiments, the electrochemical device demonstrates a long lifetime of approximately 94.0% capacity retention after 750 cycles. In some embodiments, the electrochemical device has a self-discharge rate greater than 15 mg·cm⁻¹.–2 At a surface load of 20 mA·cm –2 It retains approximately 83.5% of its capacity at high rates (~6.7 C). In some embodiments, the electrochemical device exhibits approximately 68.2% depth of discharge (DOD) and approximately 90.0% capacity retention after 2500 cycles. Attached Figure Description
[0031] The non-limiting embodiments of this disclosure will be discussed with reference to the accompanying drawings, in which: Figure 1 illustrates the inhibition of the iodine shuttle effect by 1-butyl-3-methylimidzolium methanesulfonate (BMIS): (a) the chemical structure of BMIS; (b) I3 and BMI + (c) Comparison of the charge density difference; (d) Comparison of the coulombic efficiency (CE) of batteries using electrolytes with different concentrations of BMIS; (e) Self-discharge performance (1 C = 211 mA·g) of batteries using 2 M ZnSO4 electrolyte and 2 M ZnSO4 + 0.1 M BMIS electrolyte, respectively. 1 ).
[0032] Figure 2 shows I3 The reaction between 0.02 M KI3 and 0.02 M KI3: (a) 0.02 M KI3 with water added and 0.02 M KI3 with 0.1 M BMIS added; (c) 0.02 M KI3 with water added and 0.1 M BMIS added after 12 hours.
[0033] Figure 3 depicts I3 during battery cycling and resting periods. In-situ operational analysis of the shuttle effect: In-situ UV-Vis spectra of Zn / iodine batteries using (a) 2 M ZnSO4 and (b) 2 M ZnSO4 + 0.1 M BMIS electrolytes during the first discharge process (inset shows the discharge voltage curve of the battery); In-situ Raman spectra of Zn / iodine batteries using (c) 2 M ZnSO4 and (d) 2 M ZnSO4 + 0.1 M BMIS electrolytes after the first discharge process (left panel shows the charge-discharge voltage curve of the battery); In-situ Raman spectra of Zn / iodine batteries using (e) 2 M ZnSO4 and (f) 2 M ZnSO4 + 0.1 M BMIS electrolytes during the resting process after being charged to 100% state of charge (SOC).
[0034] Figure 4 The infrared (IR) spectra of the BMIS aqueous solution before and after the addition of KI3 solution are shown.
[0035] Figure 5 The self-discharge performance of a coin cell using a 2 M ZnSO4 electrolyte was described.
[0036] Figure 6 The self-discharge performance of a coin cell using a 2 M ZnSO4 + 0.1 M BMIS electrolyte was described.
[0037] Figure 7 A quartz cell structure for in-situ UV-vis testing is shown.
[0038] Figure 8 The method for determining total I3 in 2 M ZnSO4 electrolyte is described. Calibration curve for content.
[0039] Figure 9 The Raman spectra of the battery using 2 M ZnSO4 and 2 M ZnSO4 + 0.1 M BMIS electrolytes after charging to 1.6 V are shown.
[0040] Figure 10 depicts the electrochemical performance of the Zn-I2 battery: (a) Cycling performance of the battery using 2 M ZnSO4 and 2 M ZnSO4 + 0.1 M BMIS electrolyte at 0.5 C; (b) Charge-discharge voltage curve of the battery using 2 M ZnSO4 + 0.1 M BMIS electrolyte at 0.5 C; (c) Rate performance of the battery using 2 M ZnSO4 and 2 M ZnSO4 + 0.1 M BMIS electrolyte; (d) Cycling performance of the battery using 2 M ZnSO4 + 0.1 M BMIS electrolyte at 10 C.
[0041] Figure 11 shows the charge-discharge voltage curves of batteries using (a) 2 M ZnSO4 and (b) 2 M ZnSO4 + 0.1 M BMIS electrolytes at different current densities.
[0042] Figure 12 illustrates the formation mechanism of the microsolvation layer: (a) Molecular dynamics (MD) simulation of 2 M ZnSO4 + 0.1 M BMIS electrolyte during discharge; (b) In-situ Raman test of Zn / I2 full cell during first discharge; (c) In-situ ATR-IR test of Zn / I2 full cell during first discharge; (d) Photographs of iodine electrode in BMIS / water solution at different concentrations.
[0043] Figure 13 The structure of an in-situ Raman cell is shown.
[0044] Figure 14 The structure of an in-situ ATR-FTIR cell is shown.
[0045] Figure 15 The in-situ Raman test of the Zn / I2 full cell after the first discharge was described.
[0046] Figure 16 depicts the in-situ EIS spectra of Zn / I cells using 2 M ZnSO4 and 2 M ZnSO4 + 0.1 M BMIS electrolytes at 1 C at different charge transfer resistances (Rct) in (a) the original state, (b) after discharge to 1.2 V, (c) after discharge to 1.6 V, and (d) after charging to 1.3 V.
[0047] Figure 17 depicts the CV (cyclic voltammetry) curves of Zn / I cells using (a) 2 M ZnSO4 and (b) 2 M ZnSO4 + 0.1 M BMIS electrolytes at various current densities and scan rates, and (c) the relationship between peak current and scan rate.
[0048] Figure 18 shows (a) the GITT spectrum collected at a current density of 1 C after the first discharge process; and the relationship between the diffusion coefficient and specific capacity calculated from GITT measurements during (b) the charging process and (c) the discharging process.
[0049] Figure 19 The rate performance of a pouch cell using a 2 M ZnSO4 + 0.1 M BMIS electrolyte was described.
[0050] Figure 20 depicts (a) a 1 Ah pouch cell at 8.3 mA·cm⁻¹ 2 (a) Charge-discharge voltage curves of the 1 Ah pouch cell at 8.3 mA·cm⁻¹; and (b) Charge-discharge voltage curves of the 1 Ah pouch cell at 8.3 mA·cm⁻¹. 2 The loop performance is as follows.
[0051] Figure 21 shows the Zn metal morphology after cycling in (a) 2 M ZnSO4 and (b) 2 M ZnSO4 + 0.1 M BMIS electrolyte.
[0052] Figure 22 The Cu morphology after Zn deposition is shown in (a) and (b) 2 M ZnSO4 and (c) and (d) 2 M ZnSO4 + 0.1 M BMIS electrolyte.
[0053] Figure 23 shows small-angle X-ray scattering (SAXS) images of Zn metal after cycling in (a) 2 M ZnSO4 and (b) 2 M ZnSO4 + 0.1 M BMIS electrolyte.
[0054] Figure 24 depicts the SAXS spectra of Zn metal after cycling in (a) 2 M ZnSO4 and (b) 2 M ZnSO4 + 0.1 M BMIS electrolytes.
[0055] Figure 25 shows the electrochemical performance of a high Zn depth of discharge (DOD) pouch cell using 2 M ZnSO4 + 0.1 M BMIS electrolyte: (a) at 2 mA·cm 2 (a) Electrodeposition-dissolution CE curves of Zn metal on Cu current collector under current; (b) Self-discharge performance of pouch cell at Zn DOD of 44%; (c) Self-discharge performance of pouch cell at 1.25 mA·cm⁻¹. 2 The current and cycle performance of the pouch cell at a Zn DOD of 55.1%; (d) the pouch cell at 7.94 mA·cm 2 (e) Cyclic performance of the pouch cell at 15.9 mA·cm⁻¹ with current and Zn DOD of 82.0%; 2 Current and cycling performance at Zn DOD of 68.3%.
[0056] Figure 26 The charge-discharge voltage curves of the Zn / Cu pouch cell were plotted.
[0057] Figure 27 The electrochemical performance of a Zn-I2 battery using 2 M ZnSO4 + 0.1 M 1-ethyl-3-methylimidazolium chloride electrolyte at 1 C was described.
[0058] Figure 28 The electrochemical performance of a Zn-I2 battery using 2 M ZnSO4 + 0.1 M 1-ethyl-3-methylimidazolium acetate electrolyte at 1 C was described. Detailed Implementation
[0059] As used herein, the term "electrochemical device" refers to a device capable of converting chemical energy into electrical energy through an electrochemical reaction. Examples of electrochemical devices include, but are not limited to, batteries, cells, capacitors, supercapacitors, and photovoltaic devices. The electrochemical device may be a fuel-free electrochemical device (or a non-fuel cell), or it may be an electrochemical device of a dye-sensitized solar cell (DSSC). Examples of batteries include, but are not limited to, static (non-flow) batteries or flow batteries.
[0060] As used herein, the term "ionic liquid" refers to a compound composed entirely of ions and with a melting point below 100°C. Ionic liquids consist of large organic cations and typically smaller inorganic or organic anions. In some cases, ionic liquids can have two cations, which are called dicationic ionic liquids, such as diethylene glycol-bis(3-methylimidazolium)dihydroxide.
[0061] As used in this article, the term "additive" in relation to electrolyte solutions refers to a substance present in a relatively small amount relative to the base electrolyte and used to alter or improve the performance of an electrochemical device. For example, sodium sulfate (Na₂SO₄) can be added to an H₂SO₄ electrolyte to improve its conductivity at deep discharge and low temperatures.
[0062] The term "aqueous electrolyte solution" as used in this article generally refers to an aqueous electrolyte solution or an electrolyte solution containing water as a solvent. However, this does not preclude the possibility of the presence of other components, such as electrolyte additives and organic solvents (e.g., acetone).
[0063] The term “depth of discharge (DOD)” as used herein is defined as the capacity discharged from a fully charged electrochemical device divided by the device’s nominal capacity. It represents the percentage of the electrochemical device’s discharged capacity relative to its total capacity. The depth of discharge is typically expressed as a percentage.
[0064] The term "rate performance" as used in this article refers to the ability to transfer a certain amount of specific charge (e.g., mAh·g) while maintaining a certain voltage limit. -1 (Unit: ). High rate capability enables electrochemical devices, such as mobile electronic devices, to be recharged in a very short time, thereby improving their user-friendliness.
[0065] The term "Coulomb efficiency" used in this article describes the charge efficiency of electron transfer in an electrochemical device, also known as Faraday efficiency or current efficiency. CE is defined as the quotient of discharge capacity and its prior charge capacity. It is an indicator of the reversibility of electrochemical energy storage reactions.
[0066] The term “area capacity” used in this article refers to the battery capacity delivered per unit area of the electrode.
[0067] As used herein, the term "negative electrode active material" refers to the active material used in the negative electrode of an electrochemical device. The term "positive electrode active material" refers to the active material used in the positive electrode of an electrochemical device. Active materials can be combined with other materials, such as conductive agents and components, to form a complex containing that active material, thereby preparing the desired electrode.
[0068] As used in this article, "polyiodide" refers to a class of polyhalogenated anions composed entirely of iodine atoms. Examples of polyiodides commonly involved in the shuttle effect in electrochemical devices include I3. – and I5 – .
[0069] As used in this article, "polybrominates" refers to a class of polyhalogenated anions composed entirely of bromine atoms. Examples of polybrominates commonly involved in the shuttle effect in electrochemical devices include Br3. – Br5 – and Br7 – .
[0070] This disclosure stems from the inventors' research on the shuttle effect occurring in iodine-based or bromine-based electrochemical devices. The inventors surprisingly discovered that ionic liquids can be introduced as small amounts of additives into the electrolyte solution, thereby interacting with species such as polyiodides and suppressing the shuttle effect. The inventors also surprisingly discovered that the cations of the ionic liquid accumulate on the positive electrode surface during discharge. Without being limited by any theory, the inventors believe that the cations of the ionic liquid accumulated at the positive electrode (such as 1-butyl-3-methylimidazolium cations) form a microsolvation layer on the positive electrode surface, and because iodine has high solubility in ionic liquids, the solubility of solid I2 in the microsolvation layer increases, thereby promoting I2 conversion kinetics and contributing to improved rate performance. Therefore, for iodine-based batteries, the shuttle effect is effectively mitigated or suppressed, and self-discharge resistance and cycle stability are enhanced.
[0071] Therefore, this paper discloses an ionic liquid additive for use in the electrolyte solution of an electrochemical device. The ionic liquid additive is capable of interacting with polyiodide and / or polybrominate species to mitigate the shuttle effect in the electrochemical device.
[0072] Ionic liquids are typically composed of large organic cations and small inorganic or organic anions. Most ionic liquids are soluble in a wide variety of organic and inorganic reagents and can be highly water-soluble. The number of organic cations in an ionic liquid can vary. For example, it can have one cation (i.e., a monocationic ionic liquid) or two cations (i.e., a dicationic ionic liquid).
[0073] Any suitable ionic liquid can be used in this disclosure. Mixtures of ionic liquids may be considered if desired. The inventors have found that ionic liquids with at least one heteroatom embedded in a conjugated ring can interact with polyiodides and / or polybrominates, for example, by forming NI bonds. The ability of an ionic liquid to interact with polyiodides and / or polybrominates can be preliminarily determined by a simple test: introducing the ionic liquid solution into a KI3 solution and observing whether a precipitate forms and / or whether the yellow I3 solution changes color (e.g., becomes colorless). The cations of the ionic liquid interact with polyiodides and / or polybrominates (such as I3...) The difference in charge density between the ionic liquid and the polyiodide may help determine the potential presence of such an interaction. Other methods, such as attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), can also be used to determine whether the ionic liquid can interact with polyiodides and / or polybrominates. In some cases, the cations (C16 ... + ) can form C + - I3 Interaction or C + - Br3 Interactions. For the purposes of this disclosure, the heteroatoms embedded in the conjugated ring may include, but are not limited to, nitrogen (N), sulfur (S), and / or oxygen (O). In some embodiments, the conjugated ring preferably contains nitrogen (N) as a heteroatom, which may result in the presence of amine and / or imine groups in the ionic liquid. In some other embodiments, the conjugated ring may contain both nitrogen (N) and sulfur (S) as heteroatoms.
[0074] Examples of organic cations that may be included in the ionic liquids disclosed herein include, but are not limited to, imidazolium cations, pyrazolium cations, unsubstituted or substituted oxazolium cations, thiazolium cations, pyridinium cations, and picolinium cations. In some embodiments, the ionic liquids that can be used as additives have organic cations selected from imidazolium cations, pyrazolium cations, pyridinium cations, and picolinium cations.
[0075] For illustrative purposes, the above-described organic cation may have substituents, and the substituents may be selected from alkyl, alkoxy, hydroxyalkyl, cycloalkyl, heterocycloalkyl, alkenyl, alkynyl, aryl, and heteroaryl. Preferably, the substituent may have 1 to 20 carbon atoms, for example 1 to 12 carbon atoms, 1 to 10 carbon atoms, or 1 to 8 carbon atoms. Examples of substituents on the organic cation include, but are not limited to, C1-C8 alkyl, C1-C8 alkoxy, C1-C8 hydroxyalkyl, C3-C8 cycloalkyl, C3-C8 heterocycloalkyl, C2-C8 alkenyl, C2-C8 alkynyl, C6 ...hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3-C8 hydroxyalkyl, C3 12 Aryl and C3-C 12Heteroaryl groups. In some cases, the length of substituents on an organic cation can affect the solubility of ionic liquids in a solvent. For example, when water is used as a solvent or co-solvent for an electrolyte solution, longer substituents generally result in lower solubility of the ionic liquid in the electrolyte solution. High solubility of ionic liquids is beneficial for electrolyte preparation processes.
[0076] Illustrative examples of organic cations include 1-ethyl-3-methylimidazolium ion, 1-propyl-3-methylimidazolium ion, 1-butyl-3-methylimidazolium ion, 1-pentyl-3-methylimidazolium ion, 1-hexyl-3-methylimidazolium ion, 1-ethyl-3-vinylimidazolium ion, 1-octyl-3-methylimidazolium ion, 1-allyl-3-methylimidazolium ion, 1-butyl-2-methylpyrazolium ion, 1-butylpyridinium ion, 1-pentylpyridinium ion, 1-hexyl-3-picolinium ion, 1-hexyl-4-picolinium ion, and 1-(3-hydroxypropyl)-3-methylimidazolium ion.
[0077] Examples of anions that the ionic liquids disclosed herein may contain include, but are not limited to, halide ions (such as Cl-). ,Br I ), hydroxide ions (OH) ), carboxylate ions, sulfite ions, sulfate ions (such as bisulfate and methyl sulfate ions), sulfonate ions, aminosulfonate ions, carbonate ions (such as CO3 ions), 2 and CH3CO3 ), nitrate, nitrite, perchlorate, dicyandiamide, thiocyanate, sulfonamide, antimonyate, arsenate, phosphate, phosphonate, hypophosphite, phosphite, hypophosphite, borate, and imide. In particular, the anions suitable for this disclosure can be Cl... ,Br nitrate (NO3) ), sulfate (SO4 2 ), hydrogen sulfate (HSO4) ), perchlorate (ClO4) Acetate (CH3COO) ), trifluoroacetate (CF3COO) ), trichloroacetic acid (CCl3COO) ), tetrafluoroborate (BF4) ), hexafluorophosphate (PF6) ), hexafluoroantimony (SbF6) ), hexafluoroarsenate (AsF6) ), methyl sulfate (CH3SO4) ), ethyl sulfate (C2H5SO4) ), methanesulfonate (CH3SO3) ), trifluoromethanesulfonate (CF3SO3) ), perfluorobutyrate (C4F9SO3) ), bis(fluorosulfonyl)imide ((FSO2)2N – ), bis(trifluoromethanesulfonyl)imide ((CF3SO2)2N ), heptafluorobutyrate (C3F7COO) ) and bis(pentafluoroethanesulfonyl)imide ((C2F5SO2)2N When selecting an anion, its influence on the stability of the negative electrode should be taken into account.
[0078] Besides solubility, ionic conductivity, which represents the ability of charged ions to move in an electrolyte solution, should be considered when selecting ionic liquids. For industrial applications, the price of the ionic liquid should also be considered when choosing a suitable additive.
[0079] For illustrative purposes, ionic liquids that can be used as additives may have the general formula (I): (I) Among them, R 1 R 2 R 3 R 4 and R 5 Each is independently selected from the group consisting of: H atoms and organic substituents having 1 to 20 carbon atoms, for example 1 to 12 carbon atoms or 1 to 8 carbon atoms, L - It is a compatible anion, which can correspond to the anions generally described above for ionic liquids. In some embodiments, R 2 For H, R 1 R 3 R 4 and R 5 Each is independently selected from the group consisting of an H atom and an organic substituent having 1 to 20 carbon atoms. In some further embodiments, the organic substituent having 1 to 20 carbon atoms is selected from the group consisting of alkyl, alkoxy, hydroxyalkyl, cycloalkyl, heterocycloalkyl, alkenyl, ynyl, aryl, and heteroaryl. In even further embodiments, the organic substituent having 1 to 20 carbon atoms is selected from the group consisting of C1-C8 alkyl, C1-C8 alkoxy, C1-C8 hydroxyalkyl, C3-C8 cycloalkyl, C3-C8 heterocycloalkyl, C2-C8 alkenyl, C2-C8 ynyl, C6-C 12 Aryl and C3-C 12 Mixed aromatic compounds.
[0080] Furthermore, the ionic liquids that may be applicable to this disclosure have the general formula (I'): (I') Among them, R 1 and R 3 Each is independently selected from the group consisting of: H atoms and organic groups having 1 to 20 carbon atoms, for example 1 to 12 carbon atoms or 1 to 8 carbon atoms, L - It is a compatible anion, which can correspond to the anions generally described above for ionic liquids. In some embodiments, each R 1 and R 3 Examples include H, C1-C8 alkyl, C1-C8 alkoxy, C1-C8 hydroxyalkyl, C3-C8 cycloalkyl, C3-C8 heterocycloalkyl, C2-C8 alkenyl, C2-C8 alkynyl, and C6-C 12 Aryl and C3-C 12 Mixed aryl groups. In some cases, each R... 1 and R 3 It is selected from C1-C8 alkyl, C1-C8 hydroxyalkyl and C2-C8 alkenyl.
[0081] Based on the above, the ionic liquids that may be applicable to this disclosure include, but are not limited to, the following substances: 1-Propyl-3-methylimidazolium methanesulfonate, 1-Propyl-3-methylimidazolium methyl sulfate, 1-Propyl-3-methylimidazolium trifluoromethanesulfonate, 1-Propyl-3-methylimidazolium chloride, or 1-Propyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium methanesulfonate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium methanesulfonate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Hexyl-3-methylimidazolium methanesulfonate, 1-Hexyl-3-methylimidazolium methyl sulfate, 1-Hexyl-3-methylimidazolium trifluoromethanesulfonate, 1-Hexyl-3-methylimidazolium chloride, 1-Hexyl-3-methylimidazolium tetrafluoroborate, 1-Hexyl-3-methylimidazolium acetate, or 1-Hexyl-3-methylimidazolium nitrate; 1-Octyl-3-methylimidazolium methanesulfonate, 1-Octyl-3-methylimidazolium methyl sulfate, 1-Octyl-3-methylimidazolium trifluoromethanesulfonate, 1-Octyl-3-methylimidazolium chloride, 1-Octyl-3-methylimidazolium tetrafluoroborate, 1-Octyl-3-methylimidazolium acetate, or 1-Octyl-3-methylimidazolium nitrate; 1-Ethyl-3-vinylimidazolium methanesulfonate, 1-Ethyl-3-vinylimidazolium methyl sulfate, 1-Ethyl-3-vinylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-vinylimidazolium chloride, 1-Ethyl-3-vinylimidazolium tetrafluoroborate, 1-Ethyl-3-vinylimidazolium acetate, or 1-Ethyl-3-vinylimidazolium nitrate; 1-Ethyl-3-methylimidazolium trifluoroacetate, 1-Ethyl-3-methylimidazolium methyl sulfate, 1-Ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-methylimidazolium chloride, 1-Ethyl-3-methylimidazolium tetrafluoroborate, 1-Ethyl-3-methylimidazolium acetate, or 1-Ethyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium trifluoroacetate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Butyl-2-methylpyrazolium bis(trifluoromethanesulfonyl)imine salt; 1-Butylpyridinium methanesulfonate, 1-Butylpyridinium methyl sulfate, 1-Butylpyridinium trifluoromethanesulfonate, 1-Butylpyridinium chloride, 1-Butylpyridinium tetrafluoroborate, 1-Butylpyridinium acetate, or 1-Butylpyridinium nitrate; 1-Pentylpyridinium trifluoroacetate; 1-Hexyl-3-picolinonium methanesulfonate, 1-Hexyl-3-picolinonium methyl sulfate, 1-Hexyl-3-picolinonium trifluoromethanesulfonate, 1-Hexyl-3-picolinonium chloride, 1-Hexyl-3-picolinonium tetrafluoroborate, 1-Hexyl-3-picolinonium acetate or 1-Hexyl-3-picolinonium nitrate; and 1-Hexyl-4-picolinon methanesulfonate, 1-Hexyl-4-picolinon methyl sulfate, 1-Hexyl-4-picolinon trifluoromethanesulfonate, 1-Hexyl-4-picolinon chloride, 1-Hexyl-4-picolinon tetrafluoroborate, 1-Hexyl-4-picolinon acetate, or 1-Hexyl-4-picolinon nitrate.
[0082] Ionic liquids can be prepared by methods known in the art. Imidazolium ionic liquids can be obtained by alkylating imidazoles, wherein the imidazoles can be generated by reacting amino acids, ammonia, formaldehyde, and glyoxal in an alkaline solution. Imidazoles and pyridine derivatives can also be directly alkylated in the presence of orthoesters using Brønsted acids or ammonium salts to obtain the corresponding ionic liquids in high yields with low residual chloride levels
[48] . Alternatively, the ionic liquids that can be used in this disclosure can also be obtained commercially. For example, 1-butyl-3-methylimidazolium methyl sulfate, 1-butyl-3-methylimidazolium methanesulfonate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium acetate, and 1-ethyl-3-methylimidazolium chloride are available from Sigma-Aldrich.
[0083] This article also discloses an electrolyte solution for an electrochemical device containing an ionic liquid additive. If the electrochemical device is effectively divided into two compartments and a positive electrolyte and a negative electrolyte are present, the ionic liquid is preferably contained at least in the positive electrolyte in contact with the positive electrode.
[0084] Introducing ionic liquid additives into the electrolyte solution aims to mitigate or suppress the shuttle effect caused by polyiodides and / or polybrominates in electrochemical devices. In addition to the ionic liquid additive, the electrolyte solution may further contain a solvent or a mixture of solvents, an electrolyte or a mixture of electrolytes, and / or other additives, such as additives forming the SEI (solid electrolyte interface) or pH buffers. The electrolyte solution can be aqueous (i.e., an aqueous electrolyte solution). For aqueous electrolyte solutions, aqueous solutions of potassium iodide (KI) or other iodides can be added to increase the solubility of iodine. This does not preclude the possibility of solvents other than water (e.g., acetone). If desired, organic solvents (such as tetraethylene glycol dimethyl ether) can be used to prepare the electrolyte solution.
[0085] The concentration of the ionic liquid additive can be selected to effectively interact with polyiodides and / or polybrominates and mitigate or suppress the resulting shuttle effect. However, higher concentrations of the ionic liquid additive may not be cost-effective. In some cases, the electrolyte solution contains an ionic liquid additive at a concentration of about 0.01 M to 0.5 M, or about 0.06 M to 0.15 M, or about 0.07 M to 0.12 M, or about 0.08 M to 0.10 M. For example, in a ZnSO4 aqueous electrolyte solution, the concentration of the ionic liquid can be about 0.10 M. In some embodiments, the molar ratio of the ionic liquid additive to the electrolyte is about 0.025:1 to 0.1:1, or about 0.03:1 to 0.075:1, or about 0.035:1 to 0.06:1, or about 0.04:1 to 0.05:1.
[0086] Electrolytes are used to transfer electrons between the positive (cathode) and negative (anode) electrodes. This disclosure allows for the use of any suitable electrolyte. In some cases, the electrolyte used for the negative electrode (i.e., the negative electrode electrolyte) differs from the electrolyte used for the positive electrode (i.e., the positive electrode electrolyte). Factors such as equilibrium viscosity, ionic conductivity, and control of byproducts during redox processes may play a role in the selection of the electrolyte. In some cases, it is desirable to dissolve the electrolyte in water. For example, the electrolyte may contain anions selected from SO42-. 2 NO3 ClO4 PO4 3 CO3 2 CH3COO Cl ,Br I OH bis(trifluoromethanesulfonyl)imide and trifluoromethanesulfonate. For example, the electrolyte may contain components selected from Na+. + K + Li + Mg 2+ Zn 2+ Ca 2+ And Al 3+ The cations. Accordingly, illustrative examples of electrolytes include LiOH, LiNO3, LiI, KCl, KI, K2CO3, KClO4, ZnSO4, MgNO3, Ca(NO3)2, KNO3, Li2SO4, AlCl3, ZnI2, ZnBr2, ZnCl2, ZnNO3, zinc acetate, zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2), zinc trifluoromethanesulfonate (Zn(OTf)2), Zn(ClO4)2, and combinations thereof. Mixtures of different electrolytes may produce optimized systems. For illustrative purposes, electrolyte solutions may contain electrolytes with concentrations from about 0.1 M to 10.0 M, for example, from about 0.5 M to 3.0 M, or from about 1.0 M to 2.0 M.
[0087] The pH of the electrolyte solution can be neutral (e.g., close to 7 at room temperature, such as 6.5 to 7.5). Alternatively, this can be achieved by adding some additional H+. + Ionic species can be used to alter the pH of an electrolyte, making the electrolyte solution more acidic, for example, by adding an acid (such as H₂SO₄). It is recommended to use neutral, weakly acidic, or slightly alkaline aqueous electrolyte solutions, as strong alkalinity may cause direct reactions with I₂ or Br₂.
[0088] For the purposes of this study, the electrochemical device containing the electrolyte solution can be an iodine-based electrochemical device or a bromine-based electrochemical device. Iodine-based electrochemical devices are typically based on the redox reaction of iodine, which primarily involves triiodide / iodide (I3) / I Redox pairs. Bromine-based electrochemical devices are typically based on the redox reactions of bromine, which primarily involve bromine / bromine (Br2 / Br2) redox pairs. Redox pairs. It should be understood that ionic liquid electrolyte additives and electrolyte solutions can be used in any suitable electrochemical device, such as iodine-based or bromine-based electrochemical devices. Therefore, this disclosure also provides a method for mitigating the shuttle effect caused by polyiodide and / or polybrominate substances in an electrochemical device, the method comprising introducing an ionic liquid capable of interacting with polyiodide and / or polybrominate substances as an additive into the electrolyte solution of the electrochemical device.
[0089] Electrochemical devices known in the art can also be modified to use the electrolyte solutions disclosed herein. The electrochemical device can be aqueous, and therefore an aqueous electrochemical device. In some cases, the electrochemical device can be a metal-iodine electrochemical device or a metal-bromine electrochemical device. In some embodiments, the electrochemical device is an aqueous zinc-iodine electrochemical device or an aqueous zinc-bromine electrochemical device.
[0090] Iodine and / or bromine sources can be present as positive electrode active materials in the positive electrode of an electrochemical device. Alternatively, the iodine and / or bromine sources as positive electrode active materials can be contained in the electrolyte solution in contact with the positive electrode. For example, the positive electrode may contain a certain amount of I₂ and / or LiI. In some cases, the loading of iodine sources (e.g., I₂ and LiI) on the positive electrode is from about 0.01 to about 20 mg·cm⁻¹. -2 Within the range, or the loading of bromine source (e.g., Br2 and LiBr) on the positive electrode is from about 0.01 to about 20 mg·cm⁻¹. -2 Within the range.
[0091] In some cases, the iodine and / or bromine source used as the positive electrode active material is selected from elemental iodine (I₂), LiI, NaI, KI, NH₄I, ZnI₂, quaternary ammonium iodides (such as trimethylammonium iodide), quaternary ammonium bromides (such as trimethylammonium bromide), triiodomethane (CH₃I), polyvinylpyrrolidone-iodine (PVP-I), elemental bromine (Br₂), LiBr, and combinations thereof. The negative electrode of the electrochemical device may be selected from zinc, lithium, sodium, aluminum, or magnesium sources as the negative electrode active material, such as zinc foil. If desired, electrochemical devices known in the art can be adapted to this disclosure by incorporating ionic liquid additives disclosed herein. In some embodiments, the electrochemical device is an aqueous metal-iodine electrochemical device or an aqueous metal-bromine electrochemical device.
[0092] High abundance (1.5 wt% in the Earth's crust, 0.13 wt% in seawater), high volumetric energy density (3833 mAh·cm³). 3 Magnesium (Mg) metal is a strong candidate for anode active material due to its highly negative reduction potential (-2.37 V relative to the standard hydrogen electrode), and most importantly, its highly reversible dendrite-free deposition. In this regard, the Mg-I2 battery can be referenced, where metallic magnesium is used as the anode active material, a composite of active carbon cloth (ACC) and I2 is used to prepare the cathode, and the electrolyte solution can be synthesized by in-situ reaction of bis(trimethylsilyl)aminomagnesium ((HMDS)2Mg) with aluminum chloride (AlCl3) and magnesium chloride (MgCl2) in tetraethylene glycol dimethyl ether (TEGDME).
[0093] An aluminum-iodine battery, which suffers from the polyiodide shuttle effect due to the dissolution of polyiodides in the ionic liquid electrolyte, can also be considered. For illustrative purposes, an aluminum-iodine battery may comprise aluminum foil as the negative electrode active material and I2 as the positive electrode active material, and the ionic liquid electrolyte may be a mixture of 1-ethyl-3-methylimidazolium chloride (EMIC) and AlCl3, for example, in a ratio of 1:1.3.
[0094] Water-based zinc-iodine (Zn-I2) batteries and water-based zinc-bromine (Zn-Br2) batteries could also be considered. Water-based Zn-I2 batteries benefit from the abundant iodine in seawater and have a high theoretical specific capacity (211 mAh·g). -1 ) and a high discharge plateau (relative to Zn / Zn 2+ It has an advantage in terms of specific capacity (1.38 V). Furthermore, iodine exhibits high chemical stability in most common solvents, even water. Compared to Zn-I2 batteries, aqueous Zn-Br2 batteries may have a higher theoretical specific capacity (355 mAh·g). -1 ) and a higher theoretical voltage plateau (relative to Zn / Zn 2+ It has advantages in terms of 1.85 V. When the negative electrode active material is metallic zinc, the latter can be in the form of zinc foil or copper with zinc deposited on it.
[0095] When selecting the cathode components, factors such as wettability and electronic conductivity, as well as the fixation and promotion of redox reactions (e.g., involving elements iodine, bromine, and sulfur), may need to be considered. Conductive substrates can be used in the fabrication of the cathode to load the cathode active material and enhance the cathode's conductivity. In some cases, substrates with large surface areas and pore volumes may be required. The conductive substrates used herein can be conductive carbonaceous substrates, examples of which include activated carbon, carbon black, Ketjenblack (KB), graphene, graphene oxide, carbon nanotubes (CNTs), carbon nanofibers (CNFs), carbon cloth, carbon felt, carbon paper, carbon fibers, carbon particles, carbon powder, hollow carbon spheres, metal-organic frameworks (MOFs), carbonized MOFs, activated carbon cloth / polyvinylpyrrolidone (ACC / PVPI) composites, and combinations thereof. These conductive substrates are commercially available or prepared by methods known in the art. For example, carbon nanotubes (CNTs) are commercially available (e.g., from Sigma-Aldrich) or grown using chemical vapor deposition (CVD) techniques. For the purposes of this disclosure, a positive electrode active material (such as I2) can be dissolved in a solution and then continuously adsorbed onto a conductive substrate (such as carbon cloth), thereby making the positive electrode active material uniformly distributed within the conductive substrate.
[0096] As is well known, carbon is inherently nonpolar and cannot adsorb polar substances (such as I). – and Br – Functional carbohydrates can also be introduced as the host material into the positive electrode to effectively capture guest substances (such as polyiodides or polybrominates) and limit their exposure to the electrolyte. Functional carbohydrates suitable for this purpose include, but are not limited to, polysaccharides, oligosaccharides, and combinations thereof. In this regard, the entire text of PCT / AU2023 / 050315 is incorporated herein by reference.
[0097] In the fabrication of electrochemical devices, other components such as membranes, binders, conductive agents, and current collectors can be employed. The membrane serves to provide a non-conductive barrier between the negative electrode (anode) and the positive electrode (cathode), while allowing ions to transport from one electrode to the other. It is desirable for the membrane to maintain chemical stability in the electrolyte while also exhibiting high affinity for it; good mechanical stability is also desired. Non-limiting examples of membranes include glass fiber membranes, ceramic membranes, polyolefin membranes (e.g., porous polyolefin membranes), nonwoven membranes, and porous polymer membranes.
[0098] When using powdered materials for the electrode, a binder can be added to bind the various components together and provide a uniform mixture of electrode components, thereby allowing the electrode to conduct the required number of electrons and ensuring electron contact during the cycling of the electrochemical device. Non-limiting examples of binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), and carboxymethyl cellulose (CMC).
[0099] Current collectors are bridging components used to collect the current generated at the electrodes and connect to an external circuit. They can affect the capacity, rate performance, and long-term stability of an electrochemical device. Non-limiting examples of current collectors include aluminum (Al) foil, copper (Cu) foil, carbon-coated aluminum, carbon-coated titanium (Ti) foil, and carbonaceous materials.
[0100] Electrochemical devices using the ionic liquid electrolyte additives disclosed herein offer advantages in numerous aspects, particularly in significantly improving electrochemical performance and stability. In some embodiments, the electrochemical device exhibits a low self-discharge rate of approximately 11.7% capacity loss per month at 44.0% depth of discharge and room temperature. In some embodiments, the electrochemical device exhibits a long lifetime of approximately 94.0% capacity retention after 750 cycles. In some embodiments, the electrochemical device achieves a capacity retention greater than 15 mg·cm⁻¹. 2 At a surface load of 20 mA·cm 2 At a high rate of approximately 6.7 C, the device retains approximately 83.5% of its capacity. In some embodiments, the electrochemical device exhibits approximately 68.2% depth of discharge (DOD) and approximately 90.0% capacity retention after 2500 cycles. In some embodiments, the electrochemical device exhibits 98.8% capacity retention and a high coulombic efficiency (CE) of 99.7% after 1000 cycles at 0.5 C, and demonstrates ultra-long cycling performance exceeding 15000 cycles and a capacity retention of 91.57% at 10 C. The electrochemical device employing an ionic liquid electrolyte additive can retain 182.1 mAh·g at a high current density of 10 C. 1 Significant discharge capacity.
[0101] Example Chemical reagents Zinc foil, three-electrode electrolytic cell, copper foil, aluminum-plastic film, Ag / AgCl electrode, and hydrophobic polytetrafluoroethylene (PTFE) were purchased from Shenzhen Kejing Star Technology. ZnSO4·7H2O (≥ 99.0%), iodine (≥ 99.8%), and 1-butyl-3-methylimidazolium methanesulfonate (≥ 98.0%) were purchased from Sigma-Aldrich. Ketjen Black (KB) was purchased from Guangdong Carde New Energy Technology Co., Ltd. All other reagents were of analytical grade and used directly without purification. Deionized water was used to prepare all aqueous electrolytes.
[0102] Electrode preparation Iodine (70%) and Ketjen black (30%) were mixed and ground in a mortar for half an hour. The resulting mixture was then transferred to a small glass vial and vacuum dried at 80°C for 3 hours, followed by natural cooling to obtain I2@KB. For coin cells, the positive electrode was prepared by mechanically mixing 70 wt.% I2@KB, 20 wt.% KB, and 10 wt.% polytetrafluoroethylene (PTFE) binder and dispersing it in a very small amount of ethanol solvent (AR, analytical grade). The mixture was pressed onto a titanium (Ti) mesh and dried in a vacuum oven at 50°C for 1 hour. For pouch cells, the positive electrode was prepared by mechanically mixing 80 wt.% I2@KB, 10 wt.% KB, and 10 wt.% polytetrafluoroethylene (PTFE) binder and dispersing it in a small amount of ethanol solvent (AR). The mixture was pressed onto a titanium (Ti) mesh and dried in a vacuum oven at 50°C for 1 hour.
[0103] Preparation of electrolyte 28.7 g ZnSO4·7H2O was dissolved in 50 mL of water to obtain a 2 M ZnSO4 electrolyte. The required amount of 1-butyl-3-methylimidazolium methanesulfonate (BMIS) was added to the 2 M ZnSO4 electrolyte to obtain a 2 M ZnSO4 + 0.1 (0.02, 0.05, 0.2) M BMIS electrolyte.
[0104] Electrolytes containing 2 M ZnSO4 + 0.1 M 1-ethyl-3-methylimidazolium chloride and 2 M ZnSO4 + 0.1 M 1-ethyl-3-methylimidazolium acetetate were prepared following similar steps.
[0105] Electrochemical Measurement and Materials Characterization Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed using a VMP3 (CHI 760E, Chenhua). Reaction and diffusion kinetics were analyzed using galvanostatic intermittent titration (GITT) at a current density of 0.5 C, with each charge / discharge step lasting 5 minutes and an interval of 20 minutes. Galvanostatic cycling studies were conducted at room temperature using a LAND battery testing system. The battery operating voltage relative to Zn / Zn 2+ Set to 0.6 V to 1.6 V.
[0106] Characterization In-situ attenuated total reflectance infrared (ATR-IR) spectroscopy was performed using a Thermo-Fisher Nicolet iS20 equipped with a liquid nitrogen-cooled HgCdTe (MCT) detector and a VeeMax III ATR accessory (Pike Technologies). Volatile gas H2 (HiddenHPR40) generated during battery operation was monitored at room temperature using DEMS. In-situ UV-Vis diffuse reflectance and UV-Vis absorption spectra were acquired using a UV-Vis spectrophotometer (UV2600, Shimadzu, Japan). Data were collected via SEM and EDS using a field emission scanning electron microscope (FEI Quanta 450). In-situ Raman spectroscopy of the Ni / C coating was determined using a confocal Raman microscope (Horiba LabRAM HREvolution) with a 50X (1.0 NA) objective (Olympus). The laser wavelength was 532 nm.
[0107] Molecular dynamics (MD) simulations MD simulations were performed on aqueous electrolytes with ZnSO4 salts added in different antisolvent volume ratios. The simulations were performed using the NAMD software package. [27-31] Force field parameters for all particles were obtained from the CHARMM36 force field.
[32] For H2O, the TIP3P water model was used.
[33] The time step was set to 2 fs. The cutoff radius for van der Waals forces was 12 Å, and for electrostatic interactions, it was 10 Å. Standard periodic boundary conditions were used in all simulations. After minimizing the initial structure for 5,000 steps (10 ps), each system was heated from 200 K to 300 K for 400 ps by performing Langevin kinetic temperature control. The system was further relaxed for 100 ps at 1.01325 bar using the Nosé-Hoover Langevin piston pressure control method under the NPT ensemble. After relaxation, the system was simulated for 2 ns under the canonical ensemble (NVT) for data collection and statistical analysis. The periodic boundary cell lengths (Å) are: 31.92 (x), 31.92 (y), and 35.21 (z). This solution model comprises a single-layer armchair-shaped graphene sheet with 540 carbon atoms, 40 ZnSO4 molecules, 1110 water molecules, 2 CH3SO3 molecules, and 2 C8H atoms. 15 N2 molecules. The data were presented and analyzed using visualization molecular dynamics (VMD) software
[34] .
[0108] Density functional theory (DFT) calculations First-principles calculations were performed using the Vienna Ab Initio Simulation Package (VASP) code.
[35] The Perdew-Burke-Ernzerhof functional was used to calculate the electron exchange correlation energy.
[36] Projector Augmented Wave (PAW) pseudopotentials were used to describe the ionic cores.
[37] Atomic relaxation was performed using a quasi-Newtonian minimization scheme until the maximum force on any atom was less than 0.02 eV / Å.
[38] Becke-Johnson (BJ) damping was used in the DFT-D3 method.
[39] Geometric optimization was performed at a plane wave cutoff energy of 520 eV. An irreducible 2×2×2 Monkhorst-Pack k-point grid was used,
[40] and the center was shifted to the gamma point.
[0109] Results and Discussion Figure 1a depicts the chemical structure of BMIS, which has N heteroatoms embedded in a π-conjugated ring. This is to confirm the role of BMIS in suppressing I3. The powerful shuttle effect was observed when BMIS solution was added to KI3 solution to check for precipitation. As shown in Figure 2, after the addition of BMIS solution, the originally yellow KI3 solution rapidly formed a precipitate, which became almost colorless after standing for 12 hours. This observation demonstrates the interaction between BMIS and I3 in the electrolyte. The effective interaction between them provides strong evidence. To further support this finding, BMI was investigated. + and I3 The charge density difference between them is shown in Figure 3b. Charge accumulation is shown as near I3. The yellow region represents the ion, while charge depletion is depicted as a blue region near the N atom. These results strongly suggest the formation of a Ni bond, thus confirming the BMI theory. + and I3 The conclusion was that there was an interaction between them. Furthermore, attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) was performed to investigate BMI. + and I3 Interactions between them Figure 4 ), attributed to the butyl chain [17,18], 2750 cm. 1 Up to 3000 cm 1 The stretching vibration mode peaks within the range exhibit a redshift. Furthermore, the normal CH vibration mode in the imidazole ring peaks at 3083 cm⁻¹. 1 3106 cm 1 and 3149 cm 1 The intensity at the site increases
[23] . These findings also contribute to BMI. + -I3 The existence of interactions provides strong evidence.
[0110] To evaluate the impact of BMIS additives on actual battery cycling, different concentrations of BMIS were incorporated into a 2 M ZnSO4 aqueous electrolyte. Since the coulombic efficiency (CE) at low current density is one of the most important parameters for evaluating the I2 cathode shuttle effect, the CE of Zn-I2 batteries in 2 M ZnSO4 with and without BMIS was collected at a low current density of 1 C. As shown in Figure 1c, in 2 M ZnSO4, this battery exhibited an average CE of only about 97.1%. In contrast, when the BMIS concentration increased from 0.01 M to 0.2 M, the CE significantly increased from 97.1% to 99.9%. Since the average CE of batteries with 0.1 M BMIS and 0.2 M BMIS was approximately the same, but higher BMIS concentrations would result in higher electrolyte costs, 0.1 M BMIS electrolyte was selected as the optimal concentration for this disclosure.
[0111] Besides CE, self-discharge performance can be considered another important indicator of the shuttle effect, and this was further investigated. The results show that the capacity retention rates of the battery using 2 M ZnSO4 after 12 hours, 24 hours, 48 hours, and 168 hours were 44.35%, 33.94%, 26.14%, and 17.28%, respectively (Figure 1d). Figure 5 and Figure 6 It is worth noting that the battery containing 2 M ZnSO4 + 0.1 M BMIS still maintained 89.27% capacity retention even after 168 hours, which proves that the shuttle effect was suppressed after adding BMIS.
[0112] Given the significant improvement in cycle life (CE) and the significant reduction in self-discharge exhibited by batteries containing BMIS additives, it can be concluded that BMIS effectively suppresses the shuttle effect caused by polyiodides during battery cycling. To further investigate the working mechanism of BMIS, a series of comprehensive in-situ experiments were carefully conducted. For in-situ ultraviolet-visible spectroscopy (UV-vis) testing, a specially designed self-made quartz cell was used to facilitate in-situ UV-vis measurements, such as... Figure 7 As shown in Figure 3a, the results obtained from Figure 3a indicate that when using a 2 M ZnSO4 electrolyte, the battery exhibits I3 during the initial discharge process. The significant increase in signal absorbance indicates a large amount of I3. Dissolve. According to Figure 8 The calibration curve calculations show that I3 is the highest I3 during the entire discharge process. The concentration reached approximately 0.008 mM. However, after introducing the BMIS additive into the electrolyte, as shown in Figure 3b, the I3 concentration decreased throughout the discharge process. The absorbance remained consistently at a fairly low level (approximately 0.0002 mM). This finding proves that I3 The strong interaction with the BMIS electrolyte additive resulted in a low concentration of free I3 in the electrolyte. .
[0113] Figures 3c and 3d show the in-situ Raman spectra recorded during the charge / discharge processes of batteries cycled with 2 M ZnSO4 and 2 M ZnSO4 + 0.1 M BMIS electrolytes, respectively. The spectra are approximately at 110 cm⁻¹. 1 and 160 cm 1 The Raman peaks at these locations correspond to I3. and I5 21
[19] . With 2 M ZnSO4, I3 during charging and discharging and I5 The signal appears and disappears simultaneously (Figure 3c), indicating that the iodine conversion reaction did not follow the I-C reaction. →I3 →I5 →The linear reaction pathway of I2. This may be due to I3. This is caused by the high solubility of I3, and leads to... To I5 The rapid conversion. Conversely, I3 The interaction with BMIS ensures that the reaction pathway strictly follows a linear reaction I. →I3 →I5 →I2, just like I3 Compared to the signal (which appears after charging to 1.25V), I5 The delay in signal appearance (after charging to 1.5 V) is as demonstrated (Figure 3d). Furthermore, in the battery system using 2 M ZnSO4 + 0.1 M BMIS electrolyte, I3 The blue shift of the peak also confirms I3 Interaction with BMIS ( Figure 9Furthermore, to reveal the effect of BMIS additives on self-discharge, Raman spectra were collected during the battery resting period. During the resting period, in the battery using 2 M ZnSO4, I5 It will gradually convert back to I3 Subsequently, highly soluble I3 I3 dissolves in the electrolyte and migrates to the Zn anode, leading to significant self-discharge of the battery. Finally, in the Raman spectrum, I3... and I5 The peak intensity decreased (Figure 3e). However, with the addition of BMIS, although I5 The peak intensity continued to decrease, but it is worth noting that I3 The intensity gradually increased, indicating that I3 The migration has been suppressed by BMIS.
[0114] The effects of BMIS on the cycle stability and rate performance of Zn-I2 coin cells were also investigated, with all specific capacity and current density reported based on the mass of I2 in the cell. As shown in Figures 10a and 10b, thanks to the suppression of the shuttle effect, the cell with BMIS additive exhibited an excellent long lifespan exceeding 1000 cycles when cycle stability was tested at an ultra-low current density of 0.5 C, and a high average CE of 99.7% (compared to only 92.1% for the cell using 2 M ZnSO4 electrolyte). As shown in Figures 10c and 11, the cell with BMIS additive showed a significant improvement in rate performance compared to the cell using 2 M ZnSO4 electrolyte. At a high current density of 10 C, the cell with BMIS additive maintained a rate performance of 182.1 mAh·g. 1 The discharge capacity is significantly better than that of ZnSO4-based batteries (129.4 mAh·g). 1 Furthermore, the cycling stability of the BMIS-based battery at higher current densities was investigated, as shown in Figure 10d. At 10 C, the battery achieved a remarkable capacity retention of 91.57% after an ultra-long cycle life of over 15,000 cycles, indicating the effectiveness of BMIS in stabilizing Zn-I2 performance in small-sized coin cells.
[0115] This raises an interesting question: given that the high rate performance of I2-based batteries is primarily attributed to soluble I3... So, BMIS and I3 Although the interaction between them effectively reduced I3 While BMIS is expected to improve both mobility and solubility, why does adding it to the electrolyte actually enhance rate performance? It was originally anticipated that the rate performance of the battery would be negatively impacted by the addition of BMIS. However, compared to the unmodified system, the BMIS-based system exhibits enhanced rate performance. This anomaly warrants further investigation.
[0116] Several factors could contribute to improved battery rate performance. One potential factor is catalytic effects. Certain carbon-based catalysts can lower the dissociation barrier of polyiodide / iodide conversion, thereby improving battery rate performance
[20] . However, in this system, BMIS, as an electrochemically inert ionic liquid, has not previously been reported to have any catalytic activity. Therefore, the most likely reason for the improved rate performance is the change in electrolyte structure resulting from the addition of BMIS.
[0117] As shown in Figure 12a, after dissociation in water, BMIS generates BMI. + Cations and methyl sulfate anions. After applying a negative electric field to simulate a battery discharge process, BMI... + It will migrate to the positive electrode under an electric field, which may lead to BMI. + Accumulation at the positive electrode surface. In-situ ATR-FTIR and Raman spectroscopy also confirmed the presence of BMI during discharge. + Accumulation at the positive electrode surface. Use Figure 13 The battery depicted in the figure underwent in-situ Raman testing. The result was attributed to the trans-trans (AA)
[21] conformation of the imidazolium ring, approximately 650 cm⁻¹. 1 and 750 cm 1 The intensity of the peak at this point increases with increasing depth of battery discharge (Figure 12b). This observation further confirms the BMI. + Accumulation at the surface of the I2 positive electrode. Furthermore, an in-situ ATR-FTIR signal was detected from the surface of the I2 positive electrode, such as... Figure 14 As shown. Following the discharge process, the in-plane and out-of-plane bending vibrations of the imidazole ring, approximately 1085 cm⁻¹, are attributed to this. 1 The peak at that location gradually blue-shifts (Fig. 12c). This also indicates the BMI near the cathode surface during discharge. + Increased concentration [18, 22].
[0118] BMI +Accumulation at the cathode surface can generate a microsolvated layer (MSL) with a higher concentration of ionic liquid (IL). Consequently, the solubility of iodine in this layer increases due to its higher solubility in IL. According to Figure 12d, the prepared I2 electrode was immersed in electrolytes with different concentrations of BMIS to investigate the effect of BMIS doping on the solubility of I2 in the electrolyte. Relatively low BMIS additions did not appear to effectively improve the solubility of I2. However, as mentioned above, BMI... + This process accumulates on the cathode surface to form an MSL with a higher IL ratio. This change increases the solubility of iodine in this layer, thus facilitating iodine conversion. Furthermore, in-situ Raman spectroscopy after the first discharge demonstrates that the formed MSL can be effectively retained. Figure 15 The peak intensity of the imidazolium ring remained stable during subsequent charge and discharge cycles, suggesting a BMI at the I2 cathode surface. + The concentration remained relatively stable during cycling. This stability is attributed to BMI. + and I3 The interaction between them, even under a reverse electric field, limits the BMI near the positive electrode surface. + The migration rate is [not specified]. Furthermore, considering that the amount of IL in the electrolyte remains constant, the proportion of IL in the MSL increases, while the amount in the bulk electrolyte decreases. Therefore, iodine is primarily confined within the MSL, rather than dissolving into the bulk electrolyte solution, thus preventing the loss of active material.
[0119] The conversion rate of I2 in Zn-I2 cells was further confirmed by in-situ electrochemical impedance spectroscopy (EIS). In the EIS spectrum, the semicircles in the high-frequency region correspond to the charge transfer resistance (Rct)
[23] . As shown in Figure 16, the addition of BMIS caused Rct to decrease from 125 Ω to 60 Ω, which indicates that I2 conversion rate is increased by using ionic liquid additives. A higher conversion rate to I2 was observed. Notably, the difference in Rct further increased during discharge (75 Ω to 23 Ω), indicating a further acceleration of the iodine conversion rate after BMIS accumulation at the cathode surface. Cyclic voltammetry (CV), in-situ electrochemical impedance spectroscopy (EIS), and galvanostatic intermittent titration (GITT) were used to investigate the reaction kinetics of the I2 conversion reaction after MSL formation (after the first discharge). Different scan rates (ranging from 0.1 to 0.8 mV·s) were employed. 1The CV curves of the battery under (Figure 17) support the fact that the I2 conversion rate is enhanced due to the formation of MSL. Kinetic analysis based on the log i-log ν plot reveals the slopes of the peaks in Figures 17b and 17c. Compared with the battery using 2 M ZnSO4 + 0.1 M BMIS electrolyte, the battery using 2 M ZnSO4 electrolyte shows a lower slope (for both reduction and oxidation peaks). This indicates that I2 conversion is enhanced in pure ZnSO4 electrolyte. The conversion rate to I2 was lower than that after adding BMIS. To further confirm this hypothesis, GITT was used. GITT plots were collected at a current density of 1 C (Fig. 18a), where the capacities of the two groups were similar. The diffusion coefficient (D) obtained from GITT showed a sudden drop in the voltage range of 1.3 V to 1.4 V, due to the change in I2 from liquid I3. The conversion to solid I₂. However, after the addition of BMIS, the diffusion coefficient (D) remained stable throughout the charging process, indicating that BMIS-induced MSL can improve the solubility of solid I₂ and promote the I₂ conversion reaction (Figs. 18b and 18c). In summary, the combination of in-situ Raman spectroscopy, in-situ ATR-FTIR, in-situ EIS, CV, and GITT provides a basis for the conversion of I₂ to solid I₂. + The accumulation at the I2 cathode surface, the formation of stable MSL, and the beneficial effect of MSL on battery rate performance provide compelling evidence.
[0120] To demonstrate the effectiveness of BMIS in large-scale applications, the battery was scaled up to a pouch cell. For example... Figure 19 As shown, the formation of MSL contributes to the battery's excellent rate performance, even at speeds exceeding 3 mAh·cm⁻¹. 2 This is also true even with a high positive electrode area capacity. At 20 mA·cm 2 At a high magnification of approximately 8 C, with 2 mA·cm 2 Compared to the previous version, the 0.2 Ah pouch cell still retains 83.5% of its capacity. Furthermore, this pouch cell was further scaled up to a 1 Ah capacity and an area capacity of 7.5 mA·cm². 2 A multi-layered pouch cell. As shown in Figure 20, this Ah-level pouch cell is even at 8.3 mA·cm⁻¹ 2 After 400 cycles at approximately 1.1C, the battery polarization remained stable. Furthermore, the Ah-class pouch cell achieved an impressive capacity retention of 94.0% after 750 cycles.
[0121] In practical applications, the depth of discharge (DOD) of Zn has long been a concern in pure aqueous systems. Therefore, it is reasonable to believe that BMIS may also have a beneficial effect on the Zn anode. To investigate the effect of BMIS on the utilization rate of the zinc anode in a scaled-up system, experiments were conducted using a pouch-type Zn-Cu battery. Scanning electron microscopy (SEM) images of Zn metal after cycling showed that Zn metal cycled with 2 M ZnSO4 underwent corrosion, leading to the formation of cracks and pores (Fig. 21a); in contrast, images of Zn metal cycled with 2 M ZnSO4 + 0.1 M BMIS showed a significantly smoother surface (Fig. 21b). Figure 22 The morphology of Zn deposited on Cu foil in 2 M ZnSO4 electrolyte and the prepared electrolyte solution is shown. Figure 22 a and Figure 22 In b, dendritic and aggregated Zn protrusions were observed, while Figure 22 c and Figure 22 In d, the Zn deposition is significantly more uniform. The smoother Zn morphology is attributed to the preferential adsorption of BMIS onto the (100) and (101) crystal planes, which in turn hinders Zn deposition. 2+ Ion deposition on these surfaces [24-26]. This promotes Zn deposition. 2+ Ion-selective deposition on the (002) crystal plane suppresses Zn dendrite growth. Supporting this is small-angle X-ray scattering (SAXS) images and spectra (Figs. 23 and 24) showing a significant increase in peaks associated with the (002) crystal plane after the addition of BMIS. Therefore, the addition of BMIS to the electrolyte in a Zn / Cu pouch cell at 4.0 mA·cm⁻¹... 2 The current density and 2.0 mAh·cm 2 At the area capacity, 98.9% initial CE and 99.91% average CE were achieved (Figure 25a and 25b). Figure 26 ).
[0122] Then, a pouch cell configuration with high DOD (calculated based on total Zn capacity and actual battery capacity) was tested. This pouch cell was assembled by stacking a Cu foil anode with Zn deposited, a glass fiber separator, and an I2 cathode, using a BMIS-type electrolyte. First, the self-discharge rate, a key metric for evaluating large-scale energy storage battery systems, was tested under real-world conditions. A laboratory-prepared approximately 0.2 Ah pouch cell using a BMIS-type electrolyte exhibited a self-discharge rate of 11.74% per month with a high DOD of 44.0%, outperforming mature commercial nickel-metal hydride (NiMH) batteries (20–30% per month, Figure 25b). In terms of cycle performance, the 0.27 Ah pouch cell achieved a high DOD of 55.1% and a self-discharge rate of 1.25 mA·cm⁻¹. 2 After 200 cycles at a relatively low rate (approximately 0.36 C, Figure 25c), the battery maintained a capacity retention of 93.5%. Even at an extremely high Zn DOD of 82.0%, the pouch cell maintained a high capacity retention of 94.1% after 150 cycles. Furthermore, this practical-grade pouch cell with a high DOD of 68.3% delivers 6.5 mAh·cm³. 2 The areal capacity is 15.9 mA·cm². 2 After 2,500 cycles at a relatively high rate (approximately 2.4 C), it achieved a 90.0% capacity retention and an average CE exceeding 99.996%, representing the pinnacle of stable high DOD pouch cell performance (Figure 25e and Table 1). Even compared to other commercial or quasi-commercial aqueous battery systems, this battery system demonstrates significant advantages, including energy density, lifespan, cost-effectiveness, rate performance, and acceptable self-discharge rate (Table 2).
[0123] [Table 1]: Comparison of this work with other high zinc utilization zinc pouch batteries
[0124] [Table 2]: Comparison of this work with other aqueous batteries
[0125] Achieving stable performance of zinc-based pouch cells under practical conditions, while maintaining low electrolyte cost, high DOD, and eliminating the need for complex Zn interface modification, is of great significance. The aforementioned non-limiting example introduces an ionic liquid electrolyte (e.g., BMIS) into an economical 2 M ZnSO4 electrolyte, providing a feasible strategy to suppress the iodine shuttle effect in Zn-I2 cells and improve self-discharge performance. This intervention enabled the pouch cell to achieve an excellent self-discharge rate of 11.74% capacity decay per month. Furthermore, the formation of MSL during discharge increases iodine solubility at the positive electrode surface, thereby improving the battery's rate performance even under commercial-grade areal capacity loading. Notably, compared to 2 mA·cm⁻¹… 2 Compared to the capacity at approximately 0.8 C, the areal capacity is 3 mAh·cm³. 2 The pouch battery, even at 20 mA·cm 2 Even at the stringent rate of approximately 8 C, it still maintained 83.5% capacity. BMIS also promoted Zn 2+ Selective deposition of ions on the (002) crystal plane effectively suppresses the formation of Zn dendrites. Therefore, with a high DOD of 68.2%, 6.5 mAh·cm⁻¹ 2 It achieves area capacity and 90.0% capacity retention after 2,500 cycles, with an average CE of 99.996%.
[0126] Any reference to prior art in this specification does not constitute, nor should it be construed as, an admission or implication in any way that such prior art constitutes part of common general knowledge in the art.
[0127] It should be understood that the terms “comprising” and “including” and any derivative thereof used in this specification and the appended claims are to be regarded as covering the features referred to by the terms and are not intended to exclude the existence of any additional features unless otherwise stated or implied.
[0128] In some cases, for brevity and / or to aid in understanding the scope of this disclosure, a single embodiment may combine multiple features. It should be understood that in such cases, these multiple features may be provided individually (in separate embodiments) or in any other suitable combination. Alternatively, where individual features are described in separate embodiments, these individual features may be combined into a single embodiment unless otherwise stated or implied. This also applies to the claims, which may be recombined in any combination. That is, the claims may be modified to include the features defined in any other claim. Furthermore, the phrase “at least one” in the list of items refers to any combination of these items, including a single member. As an example, “at least one of a, b, or c” is intended to cover: a, b, c, ab, ac, bc, and abc.
[0129] Those skilled in the art will understand that this disclosure is not limited in use to the specific applications described. Preferred embodiments of this disclosure are also not limited with respect to the specific elements and / or features described or depicted herein. It should be understood that this disclosure is not limited to the one or more embodiments disclosed, but is capable of various rearrangements, modifications, and substitutions without departing from the scope set forth and defined by the following claims.
[0130] References [1] a) J. Hao, L. Yuan, C. Ye, D. Chao, K. Davey, Z. Guo, SZ Qiao, Angew. Chem. Int. Ed. 2021, 60, 7366; b) SJ Zhang, J. Hao, D. Luo, PFZhang, B. Zhang, K. Davey, Z. Lin, SZ Qiao, Adv. Energy Mater. 2021, 11, 2102010. [2] a) H. Yang, Y. Qiao, Z. Chang, H. Deng, P. He, H. Zhou, Adv. Mater. 2020, 32, e2004240; b) KK Turekian, KH Wedepohl, Geol. Soc. Am. Bull. 1961, 72, 175. [3] PH Svensson, L. Kloo, Chem. Rev. 2002, 103, 1649. [4] a) L. Ma, Y. Ying, S. Chen, Z. Huang, X. Li, H. Huang, C. Zhi, Angew Chem. 2021, 60, 3791; b) B. Li, Z. Nie, M. Vijayakumar, G. Li, J. Liu,V. Sprenkle, W. Wang, Nat. Commun. 2015, 6, 6303. [5] C. Xie, Y. Liu, W. Lu, H. Zhang, X. Li, Energy Environ. Sci. 2019,12, 1834. [6] Lin, D.&Li, Y. Recent Advances of Aqueous Rechargeable Zinc-Iodine Batteries: Challenges, Solutions, and Prospects. Adv Mater 34, e2108856,doi:10.1002 / adma.202108856 (2022). [7] Zhang, S. J. et al. Polyiodide confinement by starch enablesshuttle-free Zn-iodine batteries. Adv. Mater. 34, 2201716 (2022). [8] Li, Z. et al. Long-life aqueous Zn-I2battery enabled by a low-costmultifunctional zeolite membrane separator. Nano Lett. 22, 2538-2546 (2022). [9] Liu, W. et al. Advanced Zn-I(2) Battery with Excellent CyclingStability and Good Rate Performance by a Multifunctional Iodine Host. ACS Appl Mater Interfaces14, 8955-8962, doi:10.1021 / acsami.1c21026 (2022).
[10] Si, H. et al. The electrochemical properties of iodine cathode ina novel rechargeable hydrogen ion supercapattery system with molybdenumtrioxide as anode. Electrochimica Acta 399, doi:10.1016 / j.electacta.2021.139331(2021).
[11] Ma, L. et al. Electrocatalytic iodine reduction reaction enabledby aqueous zinc-iodine battery with improved power and energydensities. Angew. Chem. Int. Ed. 60, 3791-3798, doi:10.1002 / anie.202014447(2021).
[12] Zhang, G., Wang, H., Zhang, S.&Deng, C. Using core–shellinterlinked polymer@C–iodine hollow spheres to synergistically depresspolyiodide shuttle and boost kinetics for iodine-based batteries. Journal of Materials Chemistry A 6, 9019-9031, doi:10.1039 / c8ta01470a (2018).
[13] Li, Y., Liu, L., Li, H., Cheng, F.&Chen, J. Rechargeable aqueouszinc-iodine batteries: pore confining mechanism and flexible deviceapplication. Chem Commun (Camb)54, 6792-6795, doi:10.1039 / c8cc02616e (2018).
[14] Chen, S. et al. Interface Coordination Stabilizing ReversibleRedox of Zinc for High-Performance Zinc-Iodine Batteries. Small 18, e2200168,doi:10.1002 / smll.202200168 (2022).
[15] Zhang, P.-F. et al. Tannin acid induced anticorrosive film towardstable Zn-ion batteries. Nano Energy 102, 107721 (2022).
[16] Yang, H. et al. A metal-organic framework as a multifunctionalionic sieve membrane for long-life aqueous zinc-iodide batteries. Adv. Mater. 32, 2004240 (2020).
[17] Sung, J. et al. Air–liquid interface of ionic liquid+ H2O binarysystem studied by surface tension measurement and sum-frequency generationspectroscopy. Chem. Phys. Lett. 406, 495-500 (2005).
[18] Jeon, Y. et al. Structural change of 1-butyl-3-methylimidazoliumtetrafluoroborate+ water mixtures studied by infrared vibrationalspectroscopy. The Journal of Physical Chemistry B 112, 923-928 (2008).
[19] Zhang, S. J. et al. Polyiodide Confinement by Starch EnablesShuttle‐Free Zn–Iodine Batteries. Adv. Mater. 34, 2201716 (2022).
[20] Liu, T. et al. Recognition of the catalytic activities ofgraphitic N for zinc-iodine batteries. Energy Storage Materials 53, 544-551(2022).
[21] Singh, D. K. et al. Raman Spectroscopic Study on Alkyl ChainConformation in 1‐Butyl‐3‐methylimidazolium Ionic Liquids and their AqueousMixtures. ChemPhysChem 17, 3040-3046 (2016).
[22] Cabaço, M. I., Besnard, M., Danten, Y.&Coutinho, J. Carbondioxide in 1-butyl-3-methylimidazolium acetate. I. Unusual solubilityinvestigated by Raman spectroscopy and DFT calculations. The Journal of Physical Chemistry A 116, 1605-1620 (2012).
[23] Wang, F. et al. A rechargeable aqueous Zn 2+-battery with highpower density and a long cycle-life. Energy Environ. Sci. 11, 3168-3175 (2018).
[24] Lee, D. et al.Water‐repellent ionic liquid skinny gels customizedfor aqueous Zn‐ion battery anodes. Advanced Functional Materials 31, 2103850(2021).
[25] Huang, J., Chi, X., Du, Y., Qiu, Q.&Liu, Y. Ultrastable zincanodes enabled by anti-dehydration ionic liquid polymer electrolyte foraqueous Zn batteries. ACS Applied Materials&Interfaces 13, 4008-4016 (2021).
[26] Zhang, H. et al. Inducing the Preferential Growth of Zn (002)Plane for Long Cycle Aqueous Zn‐Ion Batteries. Advanced Energy Materials 13,2203254 (2023).
[27] Plimpton, S. Fast parallel algorithms for short-range moleculardynamics. J. Comput. Phys. 117, 1-19 (1995).
[28] Jorgensen, W. L., Maxwell, D. S.&Tirado-Rives, J. Developmentand testing of the OPLS all-atom force field on conformational energetics andproperties of organic liquids. J. Am. Chem. Soc. 118, 11225-11236 (1996).
[29] Ryckaert, J.-P., Ciccotti, G.&Berendsen, H. J. Numericalintegration of the cartesian equations of motion of a system withconstraints: molecular dynamics of n-alkanes. J. Comput. Phys. 23, 327-341(1977).
[30] Hockney, R. W.&Eastwood, J. W. Computer simulation using particles .(crc Press, 2021).
[31] Nosé, S. A unified formulation of the constant temperaturemolecular dynamics methods. J. Chem. Phys. 81, 511-519 (1984).
[32] Huang, J.&MacKerell Jr, A. D. CHARMM36 all‐atom additive proteinforce field: Validation based on comparison to NMR data. J. Comput. Chem. 34,2135-2145 (2013).
[33] Mark, P.&Nilsson, L. Structure and dynamics of the TIP3P, SPC,and SPC / E water models at 298 K. J. Phys. Chem. A 105, 9954-9960 (2001).
[34] Humphrey, W., Dalke, A.&Schulten, K. VMD: visual moleculardynamics. J. Mol. Graph. Model. 14, 33-38 (1996).
[35] Hafner, J. Ab‐initio simulations of materials using VASP:Density‐functional theory and beyond. J. Comput. Chem.29, 2044-2078 (2008).
[36] Perdew, J. P., Burke, K.&Ernzerhof, M. Generalized gradientapproximation made simple. Phys. Rev. Lett. 77, 3865 (1996).
[37] Kresse, G.&Joubert, D. From ultrasoft pseudopotentials to theprojector augmented-wave method. Phys. Rev. B 59, 1758 (1999).
[38] Pfrommer, B. G., Côté, M., Louie, S. G.&Cohen, M. L. Relaxationof crystals with the quasi-Newton method. J. Comput. Phys. 131, 233-240 (1997).
[39] Grimme, S., Ehrlich, S.&Goerigk, L. Effect of the dampingfunction in dispersion corrected density functional theory. J. Comput. Chem. 32, 1456-1465 (2011).
[40] Monkhorst, H. J.&Pack, J. D. Special points for Brillouin-zoneintegrations. Physical review B 13, 5188 (1976).
[41] Hirsh, H. S. et al. Sodium‐ion batteries paving the way for gridenergy storage. Adv. Energy Mater. 10, 2001274 (2020).
[42] Dehghani-Sanij, A., Tharumalingam, E., Dusseault, M.&Fraser, R.Study of energy storage systems and environmental challenges ofbatteries. Renewable and Sustainable Energy Reviews 104, 192-208 (2019).
[43] Fan, X. et al. Battery technologies for grid-level large-scaleelectrical energy storage. Transactions of Tianjin University 26, 92-103(2020).
[44] Liu, Z. et al. Voltage issue of aqueous rechargeable metal-ionbatteries. Chem. Soc. Rev. 49, 180-232, doi:10.1039 / c9cs00131j (2020).
[45] Zhang, N. et al. Materials chemistry for rechargeable zinc-ionbatteries. Chem. Soc. Rev. 49, 4203-4219 (2020).
[46] Li, B. et al. Ambipolar zinc-polyiodide electrolyte for a high-energy density aqueous redox flow battery. Nat Commun 6, 6303, doi:10.1038 / ncomms7303 (2015).
[47] Zhao, Y., Wang, L.&Byon, H. R. High-performance rechargeablelithium-iodine batteries using triiodide / iodide redox couples in an aqueouscathode. Nat Commun 4, 1896, doi:10.1038 / ncomms2907 (2013).
[48] Kim, D.J., Oh, K.H., Park, J.K., A general and direct synthesisof imidazolium ionic liquids using orthoesters. Green Chem. , 2014,16, 4098-4101, doi.org / 10.1039 / C4GC00684D.
Claims
1. An ionic liquid additive, said ionic liquid additive being used in the electrolyte solution of an electrochemical device and capable of interacting with polyiodide and / or polybrominate species to mitigate the shuttle effect of said electrochemical device.
2. The ionic liquid additive according to claim 1, wherein, The ionic liquid additive has at least one heteroatom embedded in a conjugated ring.
3. The ionic liquid additive according to any one of claims 1 to 2, wherein, The heteroatoms are selected from nitrogen (N), sulfur (S) and oxygen (O).
4. The ionic liquid additive according to any one of claims 1 to 3, wherein, The ionic liquid is selected from the group consisting of: imidazolium ionic liquids, pyrazolium ionic liquids, oxazolium ionic liquids, thiazolium ionic liquids, pyridinium ionic liquids, and picolinium ionic liquids.
5. The ionic liquid additive according to any one of claims 1 to 4, wherein, The ionic liquid comprises anions selected from the group consisting of: halide ions, hydroxide ions, carboxylate ions, sulfite ions, sulfate ions, sulfonate ions, aminosulfonate ions, carbonate ions, nitrate ions, nitrite ions, perchlorate ions, dicyandiamide ions, thiocyanate ions, sulfonamide ions, antimony ions, arsenate ions, phosphate ions, phosphonate ions, phosphonite ions, phosphonite ions, phosphonite ions, borate ions, and imide ions.
6. The ionic liquid additive according to any one of claims 1 to 5, wherein, The ionic liquid includes anions selected from the group consisting of: Cl ,Br nitrate (NO3) ), sulfate (SO4 2 ), hydrogen sulfate (HSO4) ), perchlorate (ClO4) Acetate (CH3COO) ), trifluoroacetate (CF3COO) ), trichloroacetic acid (CCl3COO) ), tetrafluoroborate (BF4) ), hexafluorophosphate (PF6) ), hexafluoroantimonate (SbF6) ), hexafluoroarsenate (AsF6) ), methyl sulfate (CH3SO4) ), ethyl sulfate (C2H5SO4) ), methanesulfonate (CH3SO3) ), trifluoromethanesulfonate (CF3SO3) ), perfluorobutyrate (C4F9SO3) ), bis(fluorosulfonyl)imide ((FSO2)2N – ), bis(trifluoromethanesulfonyl)imide ((CF3SO2)2N ), heptafluorobutyrate (C3F7COO) ), and bis(pentafluoroethanesulfonyl)imide ((C2F5SO2)2N ).
7. The ionic liquid additive according to any one of claims 1 to 6, wherein, The ionic liquid has the general formula (I): (I) Among them, R 1 R 2 R 3 R 4 and R 5 Each is independently selected from the group consisting of: H atoms and organic substituents having 1 to 20 carbon atoms, for example 1 to 12 carbon atoms or 1 to 8 carbon atoms, L It is a compatible anion.
8. The ionic liquid additive according to claim 7, wherein, R 2 For H, R 1 R 3 R 4 and R 5 Each is independently selected from the following groups: H atoms and organic substituents having 1 to 20 carbon atoms.
9. The ionic liquid additive according to claim 8, wherein, The organic substituent having 1 to 20 carbon atoms is selected from the group consisting of alkyl, alkoxy, hydroxyalkyl, cycloalkyl, heterocycloalkyl, alkenyl, alkynyl, aryl and heteroaryl.
10. The ionic liquid additive according to any one of claims 1 to 9, wherein, The ionic liquid used as the additive comprises an organic cation selected from the group consisting of: 1-ethyl-3-methylimidazolium ion, 1-propyl-3-methylimidazolium ion, 1-butyl-3-methylimidazolium ion, 1-pentyl-3-methylimidazolium ion, 1-hexyl-3-methylimidazolium ion, 1-ethyl-3-vinylimidazolium ion, 1-octyl-3-methylimidazolium ion, 1-allyl-3-methylimidazolium ion, 1-butyl-2-methylpyrazolium ion, 1-butylpyridinium ion, 1-pentylpyridinium ion, 1-hexyl-3-picolinium ion, 1-hexyl-4-picolinium ion, and 1-(3-hydroxypropyl)-3-methylimidazolium ion.
11. The ionic liquid additive according to any one of claims 1 to 10, wherein the ionic liquid used as the additive is selected from the group consisting of: 1-Propyl-3-methylimidazolium methanesulfonate, 1-Propyl-3-methylimidazolium methyl sulfate, 1-Propyl-3-methylimidazolium trifluoromethanesulfonate, 1-Propyl-3-methylimidazolium chloride, or 1-Propyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium methanesulfonate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium methanesulfonate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Hexyl-3-methylimidazolium methanesulfonate, 1-Hexyl-3-methylimidazolium methyl sulfate, 1-Hexyl-3-methylimidazolium trifluoromethanesulfonate, 1-Hexyl-3-methylimidazolium chloride, 1-Hexyl-3-methylimidazolium tetrafluoroborate, 1-Hexyl-3-methylimidazolium acetate, or 1-Hexyl-3-methylimidazolium nitrate; 1-Octyl-3-methylimidazolium methanesulfonate, 1-Octyl-3-methylimidazolium methyl sulfate, 1-Octyl-3-methylimidazolium trifluoromethanesulfonate, 1-Octyl-3-methylimidazolium chloride, 1-Octyl-3-methylimidazolium tetrafluoroborate, 1-Octyl-3-methylimidazolium acetate, or 1-Octyl-3-methylimidazolium nitrate; 1-Ethyl-3-vinylimidazolium methanesulfonate, 1-Ethyl-3-vinylimidazolium methyl sulfate, 1-Ethyl-3-vinylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-vinylimidazolium chloride, 1-Ethyl-3-vinylimidazolium tetrafluoroborate, 1-Ethyl-3-vinylimidazolium acetate, or 1-Ethyl-3-vinylimidazolium nitrate; 1-Ethyl-3-methylimidazolium trifluoroacetate, 1-Ethyl-3-methylimidazolium methyl sulfate, 1-Ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-methylimidazolium chloride, 1-Ethyl-3-methylimidazolium tetrafluoroborate, 1-Ethyl-3-methylimidazolium acetate, or 1-Ethyl-3-methylimidazolium nitrate; 1-Butyl-3-methylimidazolium trifluoroacetate, 1-Butyl-3-methylimidazolium methyl sulfate, 1-Butyl-3-methylimidazolium trifluoromethanesulfonate, 1-Butyl-3-methylimidazolium chloride, 1-Butyl-3-methylimidazolium tetrafluoroborate, 1-Butyl-3-methylimidazolium acetate, or 1-Butyl-3-methylimidazolium nitrate; 1-Butyl-2-methylpyrazolium bis(trifluoromethanesulfonyl)imine salt; 1-Butylpyridinium methanesulfonate, 1-Butylpyridinium methyl sulfate, 1-Butylpyridinium trifluoromethanesulfonate, 1-Butylpyridinium chloride, 1-Butylpyridinium tetrafluoroborate, 1-Butylpyridinium acetate, or 1-Butylpyridinium nitrate; 1-Pentylpyridinium trifluoroacetate; 1-Hexyl-3-picolinonium methanesulfonate, 1-Hexyl-3-picolinonium methyl sulfate, 1-Hexyl-3-picolinonium trifluoromethanesulfonate, 1-Hexyl-3-picolinonium chloride, 1-Hexyl-3-picolinonium tetrafluoroborate, 1-Hexyl-3-picolinonium acetate or 1-Hexyl-3-picolinonium nitrate; and 1-Hexyl-4-picolinon methanesulfonate, 1-Hexyl-4-picolinon methyl sulfate, 1-Hexyl-4-picolinon trifluoromethanesulfonate, 1-Hexyl-4-picolinon chloride, 1-Hexyl-4-picolinon tetrafluoroborate, 1-Hexyl-4-picolinon acetate, or 1-Hexyl-4-picolinon nitrate.
12. An electrolyte solution for use in an electrochemical device, wherein, The electrolyte solution includes the ionic liquid additive according to any one of claims 1 to 11.
13. An electrochemical device, the electrochemical device comprising an electrolyte solution, wherein, The electrolyte solution includes the ionic liquid additive according to any one of claims 1 to 11.
14. The use of ionic liquids as additives in electrolyte solutions to mitigate the shuttle effect in electrochemical devices, among which, The ionic liquid additive is the ionic liquid additive according to any one of claims 1 to 11.
15. A method for mitigating the shuttle effect caused by polyiodide and / or polybrominate species in an electrochemical device, wherein, The method includes introducing an ionic liquid additive according to any one of claims 1 to 11 into the electrolyte solution of an electrochemical device.
16. The ionic liquid additive, electrolyte solution, electrochemical device, use, and method according to any one of claims 1 to 15, wherein, The electrolyte solution includes the ionic liquid additive at a concentration of 0.01M to 0.5M, or 0.06M to 0.15M, or 0.07M to 0.12M, or 0.08M to 0.10M.
17. The ionic liquid additive, electrolyte solution, electrochemical device, use, and method according to any one of claims 1 to 16, wherein, The electrolyte solution is water-based.
18. The ionic liquid additive, electrolyte solution, electrochemical device, use, and method according to any one of claims 1 to 17, wherein, The electrochemical device includes an iodine source and / or a bromine source as positive electrode active materials within the positive electrode and / or the electrolyte solution.
19. The ionic liquid additive, electrolyte solution, electrochemical device, use, and method according to any one of claims 1 to 18, wherein, The electrochemical device is selected from aqueous metal-iodine electrochemical devices and aqueous metal-bromine electrochemical devices.
20. The ionic liquid additive, electrolyte solution, electrochemical device, use, and method according to any one of claims 1 to 19, wherein: The electrochemical device exhibits a low self-discharge rate of approximately 11.7% capacity loss per month at a depth of discharge of 44.0% and at room temperature. The electrochemical device exhibits a long lifetime with approximately 94.0% capacity retention after 750 cycles; The electrochemical device operates at concentrations greater than 15 mg·cm⁻¹. –2 At a surface load of 20 mA·cm –2 (Approximately 6.7C) at high rates maintains approximately 83.5% of its capacity; and / or The electrochemical device exhibited approximately 68.2% depth of discharge (DOD) and approximately 90.0% capacity retention after 2500 cycles.